2001
DOI: 10.1159/000050944
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Composition and Lithogenic Risk in Normal Subjects following Oligomineral versus Bicarbonate-Alkaline High Calcium Mineral Water Intake

Abstract: Objective: A normal dietary calcium intake to reduce intestinal oxalate absorption is essential to avoid recurrence of calcium oxalate stone formation. It is also important in the prevention of osteopenia in idiopathic hypercalciuria. The calcium content of waters used for hydration may vary from very low to relatively high and is an important factor in prevention or additional risk of stone formation. Therefore, the effect of drinking mineral waters of different calcium concentrations on lithogenic risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…No relation was established between urinary sodium and calcium excretion, neither on standardized nor on normal dietary conditions. The majority of the studies evaluating the effect of the calcium content of water on urine composition revealed significant increases in urinary calcium excretion both in normal subjects (Rodgers, 1997;Coen et al, 2001) and stone formers (Ackermann et al, 1988;Marangella et al, 1996;Rodgers, 1997;Caudarella et al, 1998) on a high as opposed to a low calcium load with water.…”
Section: Discussionmentioning
confidence: 99%
“…No relation was established between urinary sodium and calcium excretion, neither on standardized nor on normal dietary conditions. The majority of the studies evaluating the effect of the calcium content of water on urine composition revealed significant increases in urinary calcium excretion both in normal subjects (Rodgers, 1997;Coen et al, 2001) and stone formers (Ackermann et al, 1988;Marangella et al, 1996;Rodgers, 1997;Caudarella et al, 1998) on a high as opposed to a low calcium load with water.…”
Section: Discussionmentioning
confidence: 99%
“…Bicarbonate ingestion causes changes in acid-base balance, blood pH and bicarbonate concentration in biological fluids. Coen et al (2001) suggested that consumption of bicarbonate-rich water lowers the risk of calculus formation in urine. In contrast, Lutai (1992) reported higher incidence of goiter, hypertension, ischemic heart disease, gastric and duodenal ulcers, chronic gastritis, cholecystitis and nephritis due to consumption of mineral deficient water.…”
Section: Ts Tss Tdsmentioning
confidence: 99%
“…Most of the studies focus on the total quantity of dissolved electrolyte in drinking water (Bellizzi et al, 1999;Chatterjee et al, 2012) or, more specifically, on the effects of distinct electrolytes (Panhwar et al, 2013;Siener et al, 2004). Despite the researchers efforts, the effect of water hardness on nephrolithiasis remains unclear (Schwartz et al, 2002;Coen et al, 2001;Rodgers, 1997); on the other hand, it is now generally accepted that bicarbonate-rich water have a positive effect (Karagülle et al, 2007;Bertaccini & Borghesi, 2009), probably due to increased pH which increases solubility of uric acid and urinary citrate concentration, with inhibition of calcium crystal formation and aggregation. The presence of other solutes, such as humous (humic and fulvic) acids, has also been analyzed and connected with the degradation of stones in the urinary tract (Davydova et al, 2014).…”
Section: Ion Specificity In Determining Physico-chemical Properties Omentioning
confidence: 99%